Freeman-Sheldon syndrome: a disorder of congenital myopathic origin?. Issue 3 (June 1986) - Vanĕk, J; Janda, J; Amblerová, V; Losan, F
Abstract : Freeman-Sheldon syndrome was diagnosed in an unrelated adult man and woman, with severe abnormalities of the extremities but only slight anomalies of the face. Electromyography and muscle biopsy showed a myopathy which was classified as a congenital disproportion of fibre type and seemed to be the primary cause of the deformities. This allowed classification of the syndrome as a separate type of myopathic arthrogryposis.